A new species of Centaurea (Asteraceae: sect. Psephelloideae) from Turkey - Türkloglu, I; Akan, H; Civelek, S (Blackwell Publishing Ltd, 2003)
A new species of Centaurea L. (Asteraceae), Centaurea yildizii. Civelek, I. Turkoglu & H. Akan (sect. Psephelloideae (Boiss.)) Sosn. is described from Turkey. Diagnostic characters, a description, detailed illustrations and taxonomic comments on the species are given. It is compared with the closely related taxon, Centaurea pyrrhoblephara Boiss. The geographical distribution of the new species and other related species is mapped. (C) 2003 The Linnean Society of London.
Keywords: Cardueae; Centaureinae; Compositae; taxonomy